Machinery's handbook a reference book for the mechanical engineer, designer, manufacturing engineer, draftsman, toolmaker, and machinist - Oberg, Erik, 1881-; Jones, Franklin Day, 1879-1967; Horton, Holbrook Lynedon, 1907-; Ryffel, Henry H. (Industrial Press, 2000)
Annotation A new more usable organization ... every section has been reformatted so that you will never have to search outside of that area for information on the topic you are exploring. 30% "MORE" math coverage ... from the basic to the advanced, you'll find fractions, positive and negative numbers, derivatives and integrals, analytical geometry, circular segments, matrices and engineering economics. New or revised material on ... cutting tools, screw threads, symbols and abbreviations, threads and threading, disc springs, properties and materials, sine bars, and sheet metal. Updated Standards. New individual indices for standards, materials, and interactive equations.
Includes index.
Keywords: Mechanical engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books